If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -2(x + 7) = m + 14 Reorder the terms: 3x + -2(7 + x) = m + 14 3x + (7 * -2 + x * -2) = m + 14 3x + (-14 + -2x) = m + 14 Reorder the terms: -14 + 3x + -2x = m + 14 Combine like terms: 3x + -2x = 1x -14 + 1x = m + 14 Reorder the terms: -14 + 1x = 14 + m Solving -14 + 1x = 14 + m Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '14' to each side of the equation. -14 + 14 + 1x = 14 + 14 + m Combine like terms: -14 + 14 = 0 0 + 1x = 14 + 14 + m 1x = 14 + 14 + m Combine like terms: 14 + 14 = 28 1x = 28 + m Divide each side by '1'. x = 28 + m Simplifying x = 28 + m
| 3x+2x=25-5 | | 27x^6+8=35x^3 | | 3x/5+6=4x+8 | | 5(6x+3)=-315 | | (5x+6)^2/3=(9+4x)^2/3 | | 9x-6=50 | | 1/2x-3=-4 | | y/2=8 | | 500x=600x+300 | | 2y-6=-14 | | 84*n=420 | | n/5=73 | | 14*n=42 | | 70=3z+16 | | 64*n=384 | | 9/5(191.8-273.15)+32 | | 7X-3=3X-13 | | n/3=81 | | 87=4x+7 | | n*9=63 | | n/7=21 | | 49=3x+7 | | 5x-7=30 | | 2y+3-3=-28 | | 2x-7x+8x=30 | | 5x+16=7x-20 | | 6(-5x+8)=-312 | | -7b-4=17 | | 40+7J=27 | | -37x+2=-27x-3 | | 10+5x=105 | | m-12=-16 |